Livros didáticos, imagens dos trabalhadores e ensino de História na Escola Municipal Darcy Ribeiro II(Marabá - Pa) - Silva, Carlos Patrick dos Reis (Universidade Federal do Tocantins, 2022)
This dissertation aims to understand the construction of representations through the analysis of images in the History textbook, realizing the appreciation of work as well as field workers as a theme of History and Teaching. Use textbook analysis and understanding as a method to understand issues and their perspectives in history teaching. By the way, in the school of study of the school Mara, the collection: Araribá Mais - in the books used by the textbooks of the 8th and 9th public school Darcy Ribeiro II in the field of education-PA, in the municipal context. Identifying the presence or absence of workers in visual documents. There was the cataloging of images in the didactic manual as a methodological tool, instigating the critical sense about the different representations: photography, painting, portrait, collection, woodcut, lithograph, lithograph and illustration. The exercise of criticism about the illustrations is also prioritized, as each one has its place in History and intentions. They are relevant sources for the writing of History, mainly for Cultural History. This historical study makes it indispensable for students to understand them in their artistic and social dimension of representation, which is the fundamental concept of research.